2017
DOI: 10.3892/mmr.2017.7571
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory effects of DHK-medicated serum on high glucose-induced injury in endothelial cells

Abstract: It has been shown that oxidative damage and inflammation caused by hyperglycemia in endothelial cells are key factors triggering diabetic vascular complications. The aim of the present study was to investigate the antioxidant and anti‑inflammatory effects of Danhong Huayu Koufuye (DHK)‑medicated serum on high glucose (HG)‑induced injury in endothelial cells, and examine its underlying mechanisms. EA. hy926 cells were treated with normal glucose, HG, or HG with DHK‑medicated serum. Cell viability was assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…HIF-1α is activated under hypoxia and promotes expression of genes involved in cell fate, angiogenesis, and glucose metabolism [11,12]. Zhang et al [27] have reported that blocking HIF-1α could inhibit the activation of both inflammatory response and oxidative stress. It has also been reported that overexpression of HIF-1α promotes fibrosis and contributes to CKD [28].…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α is activated under hypoxia and promotes expression of genes involved in cell fate, angiogenesis, and glucose metabolism [11,12]. Zhang et al [27] have reported that blocking HIF-1α could inhibit the activation of both inflammatory response and oxidative stress. It has also been reported that overexpression of HIF-1α promotes fibrosis and contributes to CKD [28].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, DHK is mainly used for treatment of blurred vision and sudden blindness caused by qi stagnation and blood stasis, as well as the absorption period of central retinal vein occlusion. As previous studies reported, DHK has antioxidant and anti‐inflammatory activities, and can effectively prevent deep vein thrombosis (Chen et al, ; Zhang et al, ; Zhang et al, ). However, the bioactive components of DHK are still not well understood, and current quality standards only stipulate the quantitative determination of protocatechualdehyde, which largely restricts the quality control and further development of DHK.…”
Section: Introductionmentioning
confidence: 78%